Augmentation of antidepressant effects of venlafaxine by agomelatine in mice are independent of kynurenine pathway. (October 2016) - Thomas, Jaya; Khanam, R.; Vohora, Divya
Abstract: Agomelatine is a novel antidepressant with agonistic actions at melatonergic (MT1 and MT2 receptors) and antagonistic actions at 5HT-2C receptors. Venlafaxine, a serotonin norepinephrine reuptake inhibitor, is a widely prescribed drug in depression. The present study evaluated the low dose combinations of venlafaxine and agomelatine in chronic forced swim test (chronic FST) and tail suspension test (TST) in mice. Further, the effect of above drugs and their combination was evaluated on serum pro-inflammatory cytokines and hippocampal indole amine 2, 3 dioxygenase (IDO) activity by calculating the ratios of kynurenine/tryptophan (KYN/TRP) and serotonin/tryptophan (5HT/TRP). Treatment of agomelatine (4 mg/kg, i.p.) in combination with venlafaxine (4 mg/kg, i.p.) for 3 weeks showed a significant augmenting effect on both swimming and immobility time in chronic FST and immobility time in TST as compared to animals treated with either drug alone. While venlafaxine (4 mg/kg) reversed the elevated serum levels of IL-1β and IL-6 found in chronically stressed mice, agomelatine (4 and 8 mg/kg) failed to show such a reversal. Agomelatine alone and in combination also failed to reverse the increased activity of IDO as observed by enhanced KYN/TRP and reduced 5HT/TRP seen in chronically stressed mice indicating that the augmented antidepressant effect of venlafaxine by agomelatine is not mediated by pro-inflammatory cytokine-induced activation of IDO and further, kynurenine pathway. Graphical abstract: Highlights: Agomelatine produces antidepressant effects on behavioural paradigms of depression in mice. The antidepressant effects of venlafaxine is augmented by its combination with agomelatine. Agomelatine fails to reverse the pro-inflammatory cytokines induced by chronic stress. Chronic stress enhanced KYN/TRP and reduced 5HT/TRP ratio indicating IDO activation. Agomelatine alone and in combination failed to reverse increased activity of IDO.